Utilization of Cassava Leave Flour (Manihot utilisima Pohl) Fermented Kombucha in Feed for Feed Efficiency and Growth rate of Gourami (Osphronemus gouramy) - Agussani Mendefa; Adelina Adelina; Indra Suharman (Berkala Perikanan Terubuk, 2022)
Gouramy is a freshwater fish product that has a higheconomic. But its growth is very slow so that it requires affordable, economical feed and alternative raw materials that can be used optimally, one of which is a cassava leaf. The research was held from November 2020 – Januari 2021. The purpose of this study to get the amount of cassava leaf flour (M. utilisima Pohl) fermented with kombucha in feed increase feed efficiency and growth of gouramy fry. The method used was experiment of Completely Randomized Design (RAL) with one factor, five treatments and three replications. The treatment used is the using cassava leaf flour 0, 5, 10, 15, 20% in the feed. The gourami fingerlings used are 3-5 cm and weighs 1.39±0,05 g and are in a cage measuring 1x1x1m with a stocking density of 25 fish/m3. The test diet given 3 times a day is at 07.00, 12.00 and 17.00 wib. To measure the digestibility of feed, fish maintained in an aquarium measuring 30x15x20cm and given feed test contained Cr2O3 0,5%. The results of the study that the use of fermented cassava leaf flour 20%, with feed digestibility (49.5%), protein digestibility (60.28), feed efficiency (39.45%), protein retention (24.20%) specific growth rate (3.47%), and survival (96%). The results of water quality measurements during maintenance temperature ranged from 27-30°C, pH 6.5-7.0,   DO 6.3-7.0 mg/L.